GENERAL ASPECTS REGARDING THE PRIOR DISCIPLINARY RESEARCH - ANDRA PURAN (DASCĂLU); RAMONA DUMINICĂ (Challenges of the Knowledge Society)
Disciplinary research is the first phase of the disciplinary action. According to art. 251 paragraph 1 of the Labour Code no disciplinary sanction may be ordered before performing the prior disciplinary research.These regulations provide an exception: the sanction of written warning. The current regulations in question, kept from the old regulation, provides a protection for employees against abuses made by employers, since sanctions are affecting the salary or the position held, or even the development of individual employment contract. Thus, prior research of the fact that is a misconduct, before a disciplinary sanction is applied, is an essential condition for the validity of the measure ordered. Through this study we try to highlight some general issues concerning the characteristics, processes and effects of prior disciplinary research.